2004
DOI: 10.1097/01.ta.0000140645.84897.f2
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Laparotomy to Treat Intractable Intracranial Hypertension after Traumatic Brain Injury

Abstract: Decompressive laparotomy can be a useful adjunct in the treatment of ICH failing maximal therapy following TBI. More work will need to be done to precise the exact indications for this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(55 citation statements)
references
References 25 publications
2
46
0
7
Order By: Relevance
“…(7,8) Peritoneostomy has been described as a rescue therapy for refractory intracranial hypertension patients. (17,18) This study aimed at evaluating whether intrathoracic and abdominal pressure changes, in addition to oxygenation parameters, could cause an increase in intracranial pressure values in a clinically relevant model of multiple organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…(7,8) Peritoneostomy has been described as a rescue therapy for refractory intracranial hypertension patients. (17,18) This study aimed at evaluating whether intrathoracic and abdominal pressure changes, in addition to oxygenation parameters, could cause an increase in intracranial pressure values in a clinically relevant model of multiple organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…1,[10][11] O valor considerado normal para a PIC em pacientes com TCE na UTI pode ser aceito em até 20 mmHg. A PIC média normal é considerada entre 10-15 mmHg, pressão que não causa comprometimento cerebral, isto é, não tem risco de óbito para o paciente.…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified
“…Several case reports have observed immediate reductions in ICP with decompressive laparotomy in such circumstances. A retrospective report indicated that even when abdominal compartment syndrome is not present, abdominal fascial release can reduce effectively ICP that is refractory to medical treatment [31].…”
Section: Optimizing Cerebral Venous Outflowmentioning
confidence: 99%